La dignità nel dibattito biogiuridico e biopolitico. Linee ricostruttive (TEST BioLaw Journal - Rivista di BioDiritto, 2019)
The essay summarizes the historical and philosophical debate about “dignity”, its constitutional receptions, strong points and ambiguities related to its normative use into biolaw and biopolitics.
Keywords: Dignity; biolaw and biopolitics; historical and philosophical debate; constitutional receptions; jurisprudence